Trauma and psychological distress among ethnically diverse community college students. Issue 4 (2nd April 2016) - Edman, Jeanne L.; Watson, Susan B.; Patron, David J.
ABSTRACT: An association has been found between traumatic experiences and psychological distress; however, the impact of ethnicity on psychological distress is less clear. The present study examined the relationship between traumatic experiences and measures of psychological distress among a multiethnic sample of community college students. A total of 389 male and 848 female students completed a questionnaire that included the Distressing Events Questionnaire (DEQ), the Traumatic Life Events Questionnaire (TLEQ), the Center for Epidemiologic Studies-Depression Scale (CES-D), the Bulimia (BUL), and the Drive for Thinness (DT) subscales of the Eating Disorders Inventory. As predicted, Blacks and Latinos reported higher levels of interpersonal trauma than White students. There was a positive association between trauma exposure and symptoms of depression, eating disorders, and posttraumatic stress disorder (PTSD), and no ethnic differences were observed in depression and PTSD scores among students exposed to interpersonal trauma. The high levels of trauma among Blacks and Latinos should be of concern to academic institutions because trauma is linked to poor academic performance.